One Pot Synthesis of Potentially Biologically Active Novel 4-Thiazolidinone Derivatives - Naeem, Muhammad; Nawaz Ch., Muhammad; Rehaman, Salama; Amjad, Rana (Asian Journal of Chemistry, 2012)
Novel compounds of series 1a-j and 2a-j were synthesized by adopting environment friendly methodology, with an idea that these compounds are tested for their antibacterial activity. In combination to microwave radiation with montmorillonite clays (K10 and KSF types) were used as solid phase catalysts. The catalytic efficiency of montmorillonite KSF was marginally inferior to that of montmorillonite K10. The average yield of all compounds of (1a-j) was found 88.3 and 88.5 % for the compounds (2a-j). Structural elucidation was carried out using FTIR, 1H NMR, elemental analyzer and MS. The synthesized compounds were checked for their antibacterial activity (in vivo) and found that the compounds 1g, 1h, 2g and 2j exhibited comparable or higher antibacterial activity then reference standard against E. coli, S. enteritidis, P. aeruginosa, S. aureus and B. subtilis. Most of the compounds of series-2 showed significant activity as compared with ciprofloxacin. These compounds could be lead to the selection and use as efficient antimicrobial agents, especially for the treatment of multi-drug resistant infections.